Strategi Guru dan Pembelajaran Terdiferensiasi dalam Meningkatkan Konsentrasi Belajar Siswa SMA Negeri 1 Pematangsiantar - Dearson Damanik; Monica Sirait; Claudya Rajagukguk; Reni Sihotang; Injen Pardamean Butarbutar (Young Journal of Social Sciences and Humanities, 2026)
Differentiated instruction is designed to align with students’ cognitive readiness, affective conditions, and instructional relevance, thereby enhancing their learning focus. This study employs a fieldwork approach at SMA Negeri 1 Pematangsiantar to examine how teacher strategies contribute to strengthening students’ concentration. Primary data were collected through classroom observations, interviews with teachers and students, and documentation of instructional materials; these were further enriched by teacher journal entries, students’ assessment reflections, and recorded classroom activities. The findings indicate that initial assessments enable teachers to accurately adjust task difficulty; ice-breaking activities reduce emotional tension and restore mental readiness; explicit learning objectives sharpen selective attention; and varied instructional media create a cognitive rhythm that prevents fatigue. Together, these four components operate synergistically to construct a stable architecture of attention, resulting in improved student concentration in terms of duration, depth of engagement, and consistency throughout the learning process. This article affirms that differentiated instruction, when implemented systematically, yields not only short-term improvements in student focus but also fosters more enduring attentional dispositions.